The Science of Service Systems - Demirkan, Haluk; Sphohrer, James C.; Krishna, Vikas; SpringerLink (Boston, MA Springer US, 2011)
The Science of Service Systems intends to stimulate discussion and understanding by presenting theory-based research with actionable results. Most of the articles focus on formalizing the theoretical foundations for a science of service systems, examining a wide range of substantive issues and implementations related to service science from various perspectives. From the formal (ontologies, representation specifications, decision-making and maturity models) to the informal (analysis frameworks, design heuristics, anecdotal observations), these contributions provide a snapshot in time of the gradually emerging scientific understanding of service systems. The Science of Service Systems, along with its companion text, Service Systems Implementation, is designed to present multidisciplinary and multisectoral perspectives on the nature of service systems, on research and practice in service, and on the future directions to advance service science. These two volumes compose a collection of articles from those involved in the emerging area known as service science.
Introduction of the Science of Service Systems -- Embedding the new Discipline of Service Science -- Key dimensions of Service systems in Value-Creating Networks -- Making a Science of Service Systems Practical: Seeking Usefulness and Understandability while Avoiding Unnecessary Assumptions and Restrictions -- Flexible Service Systems -- Semantics for Smart Services -- Designing Auctions for Coordination in Service Networks -- Service Systems Modeling: Concepts, Formalized Meta-Model and Technical Concretion -- Onto-ServSys:  a Service System Ontology -- A Framework that Situates Technology Research within the Field of Service Science -- Customer-Driven Value Co-Creation in Service Networks -- Towards Service System Governance ? Leveraging Service System Grammar to Empower Value Co-Creation -- Service Science ? The Opportunity to Re-think What We Know About Service Design -- Service Science Learning: Exploring the Challenge of Cross Disciplinary and Academia-Company Collaboration -- An Engineering Perspective on Service Science -- Service Systems in Changing Paradigms: An Inquiry through the Systems Sciences -- Service Customization Research: A Review and Future Directions -- Service and Science.
Electronic reproduction.
Keywords: Service science; Service industries -- Research; Service industries -- Management; Electronic books